Ontogeny and thermogenic role for sternal fat in female sheep - Henry, Belinda A.; Pope, Mark; Birtwistle, Mark; Loughnan, Rachael; Alagal, Reham; Fuller-Jackson, John-Paul; Perry, Viv; Budge, Helen; Clarke, Iain J.; Symonds, Michael E. (Oxford University Press, 2017)
Brown adipose tissue acting through a unique uncoupling protein (UCP1) has a critical role in preventing hypothermia in new-born sheep but is then considered to rapidly disappear during postnatal life. The extent to which the anatomical location of fat influences postnatal development and thermogenic function, particularly following feeding, in adulthood, are not known and were both examined in our study. Changes in gene expression of functionally important pathways (i.e. thermogenesis, development, adipogenesis and metabolism) were compared between sternal and retroperitoneal fat depots together with a representative skeletal muscle over the first month of postnatal life, coincident with the loss of brown fat and accumulation of white fat. In adult sheep, implanted temperature probes were used to characterise the thermogenic response of fat and muscle to feeding and the effects of reduced or increased adiposity. UCP1 was more abundant within sternal than retroperitoneal fat and was only retained in the sternal depot of adults. Distinct differences in the abundance of gene pathway markers were apparent between tissues, with sternal fat exhibiting some similarities with muscle that were not apparent in the retroperitoneal depot. In adults, the post-prandial rise in temperature was greater and more prolonged in sternal than retroperitoneal fat and muscle, a difference that was maintained with altered adiposity. In conclusion, sternal adipose tissue retains UCP1 into adulthood when it shows a greater thermogenic response to feeding than muscle and retroperitoneal fat. Sternal fat may be more amenable to targeted interventions that promote thermogenesis in large mammals.